Mapping Electronic Module MBKM in Indonesia: A Bibliometric Analysis - Holisoh, Ade; Pahamzah, John; Hidayat, Sholeh (IJORER : International Journal of Recent Educational Research, 2026)
This study aims to map and analyze research trends related to the MBKM (Merdeka Belajar Kampus Merdeka) E-Module in higher education by identifying publication growth, dominant themes, and research clusters during the 2020–2025 period. This research employs a qualitative descriptive approach using bibliometric analysis. Bibliographic data were collected from Google Scholar through the Publish or Perish (PoP) software using the keywords E-module, MBKM, and university. A total of 236 document metadata records published between 2020 and 2025 were obtained and stored in RIS format. The data were then analyzed using VOSviewer to generate network, overlay, and density visualizations to identify research patterns, keyword relationships, and publication trends. The findings indicate a fluctuating yet increasing trend in MBKM E-Module research, with a significant rise in publications between 2022 and 2024. The most frequently discussed topics include digital learning media, independent curriculum development, project-based learning, digital teaching materials, and student competency development. Network visualization reveals 13 distinct research clusters, demonstrating diverse research themes with strong interconnections among curriculum innovation, digital learning, and experiential learning approaches. Overlay and density visualizations show that recent studies focus increasingly on applied learning models and competency-based education. This study presents a comprehensive and longitudinal bibliometric mapping of MBKM E-Module research by systematically integrating e-module studies with the Merdeka Belajar–Kampus Merdeka (MBKM) policy in higher education. By analyzing publications from 2020 to 2025, this research reveals the intellectual structure, dominant themes, thematic evolution, and emerging research gaps within policy-driven digital learning. The findings offer novel insights into the development of MBKM-based digital learning scholarship and provide a robust reference for future empirical research, curriculum innovation, and evidence-based policy formulation in higher education.